IMPROVING PROJECT PERFORMANCE THROUGH RISK COMMUNICATION AND RISK CONTROL IN BRIDGE CONSTRUCTION KLARI WATERFALL, KARAWANG - Agung Satrio Utomo; Abdul Chalid (RADJA PUBLIKA, 2026)
The success of a construction project is greatly influenced by the ability to manage risks effectively, particularly through risk communication and risk control. This study aims to analyze the influence of risk communication and risk control on project performance in the Curug Klari Bridge construction project in Karawang. The study used a quantitative approach with a survey method. Data were obtained through questionnaires distributed to parties involved in the project implementation and analyzed using multiple linear regression with the help of IBM SPSS Statistics version 26. The results indicate that risk communication has a positive and significant effect on project performance. Risk control also has a positive and significant effect on project performance. Furthermore, risk communication and risk control simultaneously have a positive and significant effect on project performance. These findings indicate that effective risk communication and consistent risk control can improve coordination, support decision-making, minimize the impact of risks, and encourage the achievement of project objectives. Therefore, the implementation of risk communication and risk control needs to be an integrated part of project management to improve construction project performance.